2022
DOI: 10.1038/s42003-022-03800-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics and cell-specific proteomics reveals molecular signatures of sleep

Abstract: Every day, we sleep for a third of the day. Sleep is important for cognition, brain waste clearance, metabolism, and immune responses. The molecular mechanisms governing sleep are largely unknown. Here, we used a combination of single-cell RNA sequencing and cell-type-specific proteomics to interrogate the molecular underpinnings of sleep. Different cell types in three important brain regions for sleep (brainstem, cortex, and hypothalamus) exhibited diverse transcriptional responses to sleep need. Sleep restri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…While these single‐cell/single‐nuclei RNA sequencing data provide insight into the extent of interneuron diversity, the question of the extent to which these distinct CaBP‐expressing interneurons further diverge into distinct physiological, morphological, and neurochemical subclasses across cortical areas and species remains open (reviews: Li et al., 2020; Lim et al., 2018). One challenge is the fact that mRNA expression patterns revealed in these transcriptomic studies do not fully mirror neurochemical expression at the protein level (e.g., Carlyle et al., 2017; Jha et al., 2022; Parkes & Niranjan, 2019), and do not give insight on the circuit functional properties of interneurons (reviews: Batista‐Brito & Fishell, 2009; Li et al., 2020; Mi et al., 2018). Indeed, recent work in rodents has definitively shown that while interneuron identity is in large part determined by their intrinsic neurochemical and transcript expression profiles, extrinsic factors such as laminar location, connectivity, and activity play a key role in determining the function of distinct interneuron types, and ultimately shaping the cortical inhibitory circuits that underlie behavior (Boldog et al., 2018; Bugeon et al., 2022; Pouchelon et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While these single‐cell/single‐nuclei RNA sequencing data provide insight into the extent of interneuron diversity, the question of the extent to which these distinct CaBP‐expressing interneurons further diverge into distinct physiological, morphological, and neurochemical subclasses across cortical areas and species remains open (reviews: Li et al., 2020; Lim et al., 2018). One challenge is the fact that mRNA expression patterns revealed in these transcriptomic studies do not fully mirror neurochemical expression at the protein level (e.g., Carlyle et al., 2017; Jha et al., 2022; Parkes & Niranjan, 2019), and do not give insight on the circuit functional properties of interneurons (reviews: Batista‐Brito & Fishell, 2009; Li et al., 2020; Mi et al., 2018). Indeed, recent work in rodents has definitively shown that while interneuron identity is in large part determined by their intrinsic neurochemical and transcript expression profiles, extrinsic factors such as laminar location, connectivity, and activity play a key role in determining the function of distinct interneuron types, and ultimately shaping the cortical inhibitory circuits that underlie behavior (Boldog et al., 2018; Bugeon et al., 2022; Pouchelon et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we performed for the first time snRNA-seq and bulk RNA-seq in parallel with multiple independent biological replicates in response to sleep deprivation (SD) in the adult male mouse frontal cortex. Prior analyses have focused on bulk gene-level analysis [4][5][6][7][8][9][10][11][12][13]21 , or do not include independent biological replicates 22 . Thus to date it was not possible to define what may be occurring at the isoform level or to detect changes specific to particular cell types in response to SD.…”
Section: Discussionmentioning
confidence: 99%
“…The data were sourced from the GEO database and are publicly accessible under the accession number GSE137665. 44 Referring to previous literature, 44 the data underwent initial normalization and log-transformation using the NormalizeData function in Seurat. The Seurat function FindMarker was utilized to compute differential gene expression using the Wilcoxon rank-sum test method.…”
Section: Molecular and Cellular Pathways Analysismentioning
confidence: 99%